2022
DOI: 10.1055/s-0042-1742730
|View full text |Cite
|
Sign up to set email alerts
|

National Outcomes of Prophylactic Lymphovenous Bypass during Axillary Lymph Node Dissection

Abstract: Background Breast cancer treatment, including axillary lymph node excision, radiation, and chemotherapy, can cause upper extremity lymphedema, increasing morbidity and health care costs. Institutions increasingly perform prophylactic lymphovenous bypass (LVB) at the time of axillary lymph node dissection (ALND) to reduce the risk of lymphedema but reports of complications are lacking. We examine records from the American College of Surgeons (ACS) National Surgery Quality Improvement Program (NSQIP) database to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…In addition, the RATE-L risk assessment tool has yet to be externally validated on additional populations beyond its development dataset, so the risk categories presented here may not represent the true risk of lymphedema due to baseline differences between the patient populations. 18 Lastly, no patients in this study underwent surgical treatment or prevention of lymphedema, which have been shown to be safe and effective procedures that significantly improve quality of life 37,38 ; further study may elucidate a disparity in the utilization of these newer, more complex treatment techniques.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the RATE-L risk assessment tool has yet to be externally validated on additional populations beyond its development dataset, so the risk categories presented here may not represent the true risk of lymphedema due to baseline differences between the patient populations. 18 Lastly, no patients in this study underwent surgical treatment or prevention of lymphedema, which have been shown to be safe and effective procedures that significantly improve quality of life 37,38 ; further study may elucidate a disparity in the utilization of these newer, more complex treatment techniques.…”
Section: Discussionmentioning
confidence: 96%
“…The decision to do ILR has been shown to be safe, but it does increase the operative time by an average of 99.2 minutes (approximately a 40 minute reduction in additional operative time related to ILR previously reported). 13 A large portion of that time is consumed by the setup of the microsurgery instruments and microscope.…”
Section: Discussionmentioning
confidence: 99%
“…The decision to do ILR has been shown to be safe, but it does increase the operative time by an average of 99.2 minutes (approximately a 40-minute reduction in additional operative time related to ILR previously reported). 13 A large portion of that time is consumed by the setup of the microsurgery instruments and microscope. Both in evidenced-based literature as well as in our institution's study population, the majority of patients who develop BCRL, do so in the first 2 years after their ALND.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are currently no consensus guidelines for billing and coding for many lymphedema procedures such as ILR. Some sources use CPT codes 35 206, 38 999, and 38 308 for ILR, while the authors have also used 75 801 and 69 990 to bill for this procedure 33,38 . As insurance coverage for ILR increases and its use becomes more widespread, this will undoubtedly help to standardize billing practices.…”
Section: Discussionmentioning
confidence: 99%